IFNs in host defence and parasite immune evasion during Toxoplasma gondii infections - Lüder, Carsten G. K. (Frontiers in Immunology, 2024)
Interferons (IFNs) are a family of cytokines with diverse functions in host resistance to pathogens and in immune regulation. Type II IFN, i.e. IFN-γ, is widely recognized as a major mediator of resistance to intracellular pathogens, including the protozoan Toxoplasma gondii. More recently, IFN-α/β, i.e. type I IFNs, and IFN-λ (type III IFN) have been identified to also play important roles during T. gondii infections. This parasite is a widespread pathogen of humans and animals, and it is a model organism to study cell-mediated immune responses to intracellular infection. Its success depends, among other factors, on the ability to counteract the IFN system, both at the level of IFNmediated gene expression and at the level of IFN-regulated effector molecules. Here, I review recent advances in our understanding of the molecular mechanisms underlying IFN-mediated host resistance and immune regulation during T. gondii infections. I also discuss those mechanisms that T. gondii has evolved to efficiently evade IFN-mediated immunity. Knowledge of these fascinating host-parasite interactions and their underlying signaling machineries is crucial for a deeper understanding of the pathogenesis of toxoplasmosis, and it might also identify potential targets of parasite-directed or host-directed supportive therapies to combat the parasite more effectively.